Tumor-Associated Extracellular Matrix: How to Be a Potential Aide to Anti-tumor Immunotherapy? - He, Yingying; Liu, Tao; Dai, Shuang; Xu, Zihan; Wang, Li; Luo, Feng (Frontiers in Cell and Developmental Biology, 2021)
The development of cancer immunotherapy, particularly immune checkpoint blockade therapy, has made major breakthroughs in the therapy of cancers. However, less than one-third of the cancer patients obtain significant and long-lasting therapeutic effects by cancer immunotherapy. Over the past few decades, cancer-related inflammations have been gradually more familiar to us. It’s known that chronic inflammation in tumor microenvironment (TME) plays a predominant role in tumor immunosuppression. Tumor-associated extracellular matrix (ECM), as a core member of TME, has been a research hotspot recently. A growing number of studies indicate that tumor-associated ECM is one of the major obstacles to realizing more successful cases of cancer immunotherapy. In this review, we discussed the potential application of tumor-associated ECM in the cancer immunity and its aide potentialities to anti-tumor immunotherapy.